Predictors of Outcome for Aortic Valve Reimplantation Including the Surgeon—A Single-Center Experience - Tkebuchava, Sophie; Tasar, Raphael; Lehmann, Thomas; Faerber, Gloria; Diab, Mahmoud; Breuer, Martin; Franke, Ulrich; Kirov, Hristo; Gummert, Jan; Lichtenberg, Artur; Wahlers, Thorsten; Doenst, Torsten (The Thoracic and Cardiovascular Surgeon, 2018)
Introduction Aortic valve reimplantation is considered technically demanding. We searched for predictors of long-term outcome including the surgeon as risk factor.Methods We selected all aortic valve reimplantations performed in our department between December 1999 and January 2017 and obtained a complete follow-up. The main indications were combined aortic aneurysm plus aortic valve regurgitation (AR), 69% and aortic dissections (15%). In 14%, valves were bicuspid. Cusp repair was performed in 27% of patients. One-third received additional procedures (coronary artery bypass grafting, mitral, or arch surgery). We performed multivariable analyses for independent risk factors of short- and long-term outcomes, including “surgeon” as variable. Twelve different surgeons operated on 193 patients. We created three groups: surgeons A and B with 84 and 64 procedures, respectively, and surgeon C (10 surgeons for 45 patients).Results Cardiopulmonary bypass and clamp times were 176 ± 45 and 130 ± 24 minutes, respectively. In-hospital mortality was 2%. Postoperatively, 5% had mild and 0.5% had moderate AR. Kaplan–Meier's survival estimates, freedom from reoperation, and freedom from severe AR at 12 years were 97 ± 1, 93 ± 2, and 91 ± 3%, respectively. Age and chronic obstructive pulmonary disease appeared as risk factors for perioperative complications by univariate analysis. Age, coronary artery disease, and duration of cardiopulmonary bypass, but not surgeon, presented as risk factors by multivariable analysis.Conclusion The results suggest that if a David procedure is performed successfully, long-term durability may be excellent. They also suggest that good and durable results are possible even with limited experience of the operating surgeon.
Keywords: aortic valve reconstruction; David operation; risk factors; cardiac surgery